Rumour and social stigma as barriers to the prevention of coronavirus disease (COVID-19): What solutions to consider? - Md. Nazmul Huda; Rubana Islam; Mohammed Owais Qureshi; Sunitha Pillai; Syeda Zakia Hossain (University of New South Wales, 2020)
Globally, multiple factors have elevated the risk and contributed to the fast spread of COVID-19. Alongside this, unsolicited rumours and social stigma are believed to be two possible barriers to the effective prevention of the disease. Despite measures taken, rumours and social stigma related to COVID-19 tend to increase globally. Several studies document that rumours and social stigma may fuel the risk and rapid spread of COVID-19. However, how these rumours and social stigma act as barriers to the prevention of the COVID-19 outbreak remain unclear. This article aims to discuss how rumours and social stigma can undermine the preventive and clinical efforts to fight against the spread of COVID-19 and suggest potential policy implications for addressing rumours and social stigma and optimising preventive efforts. A narrative review of secondary sources of data, including published studies, grey literature and authentic press reports was conducted. The analysis indicates that unverified rumours associated with COVID-19 may weaken people's preparedness for a new infectious disease by driving them to wrong treatment and preventing them from adhering to evidence-based medical suggestions and treatment. Findings also suggest that social stigma may reduce healthcare workers' agency and self-respect to provide support, treatment and care for those with COVID-19. Social stigma may also constrain participation in screening, testing, quarantine, isolation, and treatment of the disease. This article offers six potential policy pathways and emphasises the national and international coordination of all stakeholders for addressing rumours and social stigma associated with COVID-19.